2018
DOI: 10.1016/j.jinorgbio.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo evaluation of the response of Galleria mellonella larvae to novel copper(II) phenanthroline-phenazine complexes

Abstract: Herein we report the in-vivo characterisation and metabolic changes in Galleria mellonella larvae to a series of bis-chelate copper(II) phenanthroline-phenazine cationic complexes of [Cu(phen)] (Cu-Phen), [Cu(DPQ)(Phen)] (Cu-DPQ-Phen) and [Cu(DPPZ)(Phen)] (Cu-DPPZ-Phen) (where phen = 1,10-phenanthroline, DPQ = dipyrido[3,2-ƒ:2',3'-h]quinoxaline and DPPZ = dipyrido[3,2-a:2',3'-c]phenazine). Our aim was to investigate the influence of the systematic extension of the ligated phenazine ligand in the G. mellonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In this study, we noted how these genes were increasingly up-regulated at higher fipronil concentrations, indicating that high-dose pesticide stress may demand parasitic wasp larvae a large amount of energy in order to reduce damage to development. Similarly to our findings, previous research has reported that sugar-related metabolic pathways in insects are up-regulated in the presence of insecticide stress (Rochford et al, 2018;Zhang et al, 2021). The neuroactive ligand-receptor interaction pathway transduces different signals such as biogenic amines, neuropeptides, and lipoproteins and regulates insect development and homeostasis (Kwon et al, 2016;Dong et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we noted how these genes were increasingly up-regulated at higher fipronil concentrations, indicating that high-dose pesticide stress may demand parasitic wasp larvae a large amount of energy in order to reduce damage to development. Similarly to our findings, previous research has reported that sugar-related metabolic pathways in insects are up-regulated in the presence of insecticide stress (Rochford et al, 2018;Zhang et al, 2021). The neuroactive ligand-receptor interaction pathway transduces different signals such as biogenic amines, neuropeptides, and lipoproteins and regulates insect development and homeostasis (Kwon et al, 2016;Dong et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Over the past two decades, transition metal complexes have had a revival of interest as possible alternatives or adjuvants to the current arsenal of antimicrobial agents, and in particular due to the rapid emergence of resistant microorganisms occurring worldwide [ 13 ]. Novel inorganic complexes with 1,10-phenanthroline (phen) ligands have demonstrated promising therapeutic capabilities with diverse biological activity, including anticancer [ 14 , 15 ], antifungal [ 16 , 17 ], antibacterial [ 18 , 19 ] and antiviral [ 20 ] capabilities. In a recent review, we have reported on the research that points to the potential of metal-phenanthroline complexes as alternative therapeutics in this era of antibiotic resistance [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, complexes Mn-tdda-phen and Ag-tdda-phen induced no mortality at 15 µg/larvae (20.39 and 12.5 µM, respectively) while doubling the concentration (40.78 and 24.9 µM, respectively) resulted in 6.66 ± 5.77% death for the former and 23.33 ± 5.77% death for the latter, after exposure for 72 h. Cu-tdda-phen was the most toxic to the larvae, a concentration of 15 µg/larvae (20.15 µM) resulted in a mortality rate of 53.33 ± 5.77% after 72 h and increasing the dose to 30 µg/larvae (40.3 µM) saw complete death of all tested larvae after the same amount of time. It is well known that copper is highly toxic to mammals, and similar studies investigating Cu-phen complexes and their derivatives have also highlighted their lethality towards G. mellonella [ 28 , 35 ]. Although lower concentrations of Cu-tdda-phen did not induce mortality, moderate to severe melanization was observed.…”
Section: Resultsmentioning
confidence: 99%
“…They have a relatively short life cycle (40–60 days), and can survive at 37 °C which is an important attribute when assessing virulence and treatment of human pathogens [ 30 ]. Therefore, G. mellonella has been extensively utilized to evaluate the pathogenicity of bacterial and fungal pathogens [ 31 , 32 , 33 ], study biofilm formation [ 34 ], measure the in vivo toxicity of novel compounds [ 35 , 36 ], and determine the in vivo efficacy of established [ 37 , 38 ] and novel [ 19 , 39 ] antimicrobial agents. Moreover, studies assessing G. mellonella and mammalian models have reported a correlation in results obtained.…”
Section: Introductionmentioning
confidence: 99%